Atmospheric cold plasma interactions with modified atmosphere packaging inducer gases for safe food preservation. (December 2016) - Han, L.; Boehm, D.; Amias, E.; Milosavljević, V.; Cullen, P.J.; Bourke, P.
Abstract: Diverse microbiological challenges and pervasive microbial resistance drive technological development in food processing, where increasing process complexity and consumer demand for less processed goods leads to strong demand for effective decontamination. Atmospheric cold plasma (ACP) has wide potential for decontamination application in the food sector. We investigated the effect of Modified Atmosphere Packaging (MAP) gas mixtures on reactive species generated, their efficacy and mechanism of inactivation against Escherichia coli, Listeria monocytogenes and Staphylococcus aureus . Oxygen levels in the applied working gas had positive interactive effects on ROS generation, in-package inactivation efficacy in conjunction with post-treatment storage time. Listeria populations were undetectable after 15 s treatment with high Oxygen MAP mix using 24 h post-treatment storage time. However, RNS generation and effect was dependent on the nitrogen content but also on the presence of oxygen. Different modes of interaction of ROS and RNS with Gram positive and Gram negative bacteria were observed. Highlights: Atmospheric cold plasma is effective for inactivation of food microbial challenges. Both process and target parameters govern inactivation efficacy. Oxygen composition in the applied working gas governs inactivation efficacy. Nitrogen composition in the applied working gas has synergistic effect with oxygen.